Convergences between the Brazilian National Health Plan and scientific articles on Neglected Tropical Diseases - Sobral, Natanael Vitor; Morais, Viviane Martha Santos de; Bufrem, Leilah Santiago; Santos, Raimundo Nonato Macedo dos; Silva, Fabio Mascarenhas e (RECIIS, 2021)
In Brazil, the National Health Plan (NHP) was the central instrument for public health planning from 2016 to 2019. In this paper, we show that there is a convergence between the Plan and the publication of scientific articles written by institutional researchers in the context of Neglected Tropical Diseases. The methodology used consisted of the following stages: identification of the universe of researchers, data collection, thematic characterization of Neglected Tropical Diseases in the Plan, organization of information, and production of indicators. In total, there were 2,719 researchers and 18,023 journal articles from 2015 to 2018. Of these, 2,541 articles, or 14.09%, were related to Neglected Tropical Diseases. Regarding the convergences, there was strong alignment with leishmaniasis, Chagas disease, dengue, leprosy, schistosomiasis, and Chikungunya fever. However, the coverage of topics by scientific publications was broader than that of the political instrument due to the inclusion of other themes: snake bites, helminthiasis and lymphatic filariasis.